Empowering Economic Independence through Entrepreneurship Training for Dasa Wisma Mothers - Rahmawati, Rahmawati; Markhumah, Umatun; Amperawati, Endang Dwi; Widayani, Astrid; Nurlaela, Siti; Arifah, Siti; Iswara, Dewi (Jurnal IPTEK Bagi Masyarakat, 2025)
Economic empowerment of women in the dasa wisma group is crucial for improving their welfare and promoting economic independence. Therefore, efforts are needed to empower the economy of this group. This community service activity aims to empower the economic independence of women in the dasa wisma group in Pandes Village, Wedi District, Klaten Regency by providing basic business entrepreneurship training. The training method was conducted with 20 women in the dasa wisma group. It began with data collection through a survey of the training participants aimed at measuring their level of knowledge, skills, motivation, and entrepreneurial initiative before and after the training. The results of this basic business entrepreneurship training activity showed a positive and significant impact on the participants. There was a substantial increase in entrepreneurial knowledge and skills among the women in the dasa wisma group, with an average score increase of 29%. In addition, this training significantly contributed to increasing participants' motivation and initiative in starting or developing their micro-businesses. This business entrepreneurship training program proved to be an effective economic empowerment strategy for the dasa wisma group of women. The implication is the importance of a structured and sustainable entrepreneurship training program. It is recommended that further activities consider the factors supporting and inhibiting business sustainability after training, to ensure maximum long-term impact.